Positive electrode sheets and lithium-ion batteries

JP2025505287AActive Publication Date: 2025-02-21BYD CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024547934
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-02-15
Filing Date
2023-02-07
Publication Date
2025-02-21
Estimated Expiration
2043-02-07

AI Technical Summary

Benefits of technology

【0085】 本開示の有益な効果を強調するために、以下の比較例が提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025505287000001_ABST
    Figure 2025505287000001_ABST
Patent Text Reader

Abstract

A positive electrode sheet and a lithium-ion battery having the positive electrode sheet are provided. The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector. The positive electrode active material layer includes a positive electrode active material. The positive electrode active material includes a first lithium iron phosphate material and a second lithium iron phosphate material. When the cumulative volume distribution percentage of the first lithium iron phosphate material is 50%, the particle size is D 1 v When the cumulative volume distribution percentage of the second lithium iron phosphate material is 50%, the particle size is D 2 v 50μm. D 1 v 50 is in the range of 0.3 to 0.95, D 2 v When the volume density of the positive electrode active material reaches a maximum value, the particle size is D mo μm, and the compressed density of the positive electrode sheet is PDg / cm under a pressure of 1.5Mpa. 3 0.45≦PD×D mo ≦12.38.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This disclosure claims priority to Chinese Patent Application No. 202210139512.0, entitled “Positive electrode sheet and lithium ion battery,” filed on February 15, 2022, the entire contents of which are incorporated herein by reference.

[0002] The present disclosure relates to the field of lithium-ion batteries, and more particularly to positive electrode sheets and lithium-ion batteries. [Background technology]

[0003] Lithium iron phosphate materials are widely used due to their advantages such as high safety, low cost, and environmental friendliness. However, lithium iron phosphate materials also have obvious drawbacks. That is, the pressed density of lithium iron phosphate materials is low, which leads to low energy density of batteries made with lithium iron phosphate materials, and therefore cannot meet the demand for batteries with long battery life. In order to improve the energy density of batteries, lithium iron phosphate materials with high pressed density are needed. However, as the pressed density of lithium iron phosphate materials increases, the electrochemical performance of the batteries often decreases. Summary of the Invention [Means for solving the problem]

[0004] In a first aspect, the present disclosure provides a cathode sheet including a cathode current collector and an active cathode material layer disposed on at least one side of the cathode current collector. The active cathode material layer includes an active cathode material, the active cathode material including a first lithium iron phosphate material and a second lithium iron phosphate material. When the cumulative volume distribution percentage of the first lithium iron phosphate material is 50%, the corresponding particle size is D 1 v When the cumulative volume distribution percentage of the second lithium iron phosphate material is 50%, the corresponding particle size is D2 v 50μm. D 1 v 50 is in the range of 0.3 to 0.95, D 2 v When the volume density of the positive electrode active material reaches a maximum value, the corresponding particle size is D mo The compressed density of the positive electrode sheet is PDg / cm under a pressure of 1.5Mpa. 3 and PD is 0.45≦PD×D mo <= 12.38.

[0005] In some embodiments of the present disclosure, PD is in the range of 2.25 to 2.85.

[0006] In some embodiments of the present disclosure, PD is in the range of 2.3 to 2.7.

[0007] In some embodiments of the present disclosure, PD is in the range of 2.35 to 2.7.

[0008] In some embodiments of the present disclosure, the first lithium iron phosphate material D 1 v 50 is in the range of 0.35 to 0.65, and the D of the second lithium iron phosphate material 2 v 50 is in the range of 1.25 to 2.85.

[0009] In some embodiments of the present disclosure, PD×D mo is in the range of 0.6 to 10.5.

[0010] In some embodiments of the present disclosure, D mo is in the range of 0.2 to 4.5.

[0011] In some embodiments of the present disclosure, D mo is in the range of 0.3 to 4.2.

[0012] In some embodiments of the present disclosure, when the cumulative volume distribution percentage of the positive electrode active material is 50%, the corresponding particle size is D v50 μm (median particle size), D v 50 is in the range of 0.2 to 3.1.

[0013] In some embodiments of the present disclosure, the mixing weight ratio of the first lithium iron phosphate material to the second lithium iron phosphate material is in the range of 1:(1 to 9).

[0014] In some embodiments of the present disclosure, the first lithium iron phosphate material has a carbon coating layer on a surface thereof and / or the second lithium iron phosphate material has a carbon coating layer on a surface thereof.

[0015] In some embodiments of the present disclosure, the positive electrode active material layer further includes a binder and a conductive agent. The compressed density of the positive electrode sheet is 2.25 to 2.75 g / cm under a pressure of 1.5 MPa. 3 is in the range.

[0016] In some embodiments of the present disclosure, the positive electrode active material layer is formed by coating a positive electrode paste, which includes a positive electrode active material, a conductive agent, a binder, and a solvent, onto a positive electrode current collector.

[0017] In a second aspect, the present disclosure provides a lithium-ion battery comprising a positive electrode sheet as described in the first aspect of the present disclosure.

[0018] In some embodiments of the present disclosure, the lithium-ion battery further includes a negative electrode sheet, and an electrolyte and a separator positioned between the positive and negative electrode sheets. [Brief description of the drawings]

[0019] [Figure 1] FIG. 2 is a graph showing cycle performance curves of each of the pouch batteries of Examples 1 to 5 and Comparative Example 1 of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] The above description is some embodiments of the present disclosure. It should be noted that some improvements and modifications may be made by those skilled in the art without departing from the principle of the present disclosure, and they fall within the protection scope of the present disclosure.

[0021] The present disclosure provides a positive electrode sheet and a method for preparing the same, which ensures that the positive electrode sheet has a high packing density, and the battery prepared therewith has good electrochemical performance.

[0022] In a first aspect, the present disclosure provides a cathode sheet including a cathode current collector and an active cathode material layer disposed on at least one side of the cathode current collector. The active cathode material layer includes an active cathode material, the active cathode material including a first lithium iron phosphate material and a second lithium iron phosphate material. When the cumulative volume distribution percentage of the first lithium iron phosphate material is 50%, the corresponding particle size is D 1 v When the cumulative volume distribution percentage of the second lithium iron phosphate material is 50%, the corresponding particle size is D 2 v 50μm. D 1 v 50 is in the range of 0.3 to 0.95, D 2 v When the volume density of the positive electrode active material reaches a maximum value, the corresponding particle size is D mo The compressed density of the positive electrode sheet is PDg / cm under a pressure of 1.5Mpa. 3 and PD is 0.45≦PD×D mo <= 12.38.

[0023] In the present disclosure, two lithium iron phosphate materials having different particle sizes are used, and the particle size D of the positive electrode active material obtained after mixing is mo The mixing ratio of the two lithium iron phosphate materials is adjusted so that the particle size D of the first lithium iron phosphate material and the compressed density PD of the positive electrode sheet satisfy a specific relationship. This ensures that the positive electrode sheet has an appropriately high compressed density and that the electrochemical performance (especially the cycle performance) of the battery made using this positive electrode sheet is excellent.1 v 50, the particle size D of the second lithium iron phosphate material 2 v 50, and the particle size of the positive electrode active material D mo may be obtained from the respective laser particle size distribution diagrams. The test method can be found in GB / T19077-2016 / ISO13320:2009: Laser diffraction method for particle size analysis. The test equipment is a laser particle size analyzer (such as Malvern3000). When the cumulative volume distribution percentage of the material is 50%, the corresponding particle size is called the median particle size of the material. PD may be obtained by testing the positive electrode sheet by a compression machine.

[0024] In some embodiments of the present disclosure, PD is in the range of 2.25 to 2.85. In this case, the positive electrode sheet has a thickness of PD×D mo is in the range of 0.45 to 12.38, the positive electrode sheet has a large compressed density and an appropriate porosity, and the battery has further good cycle performance and rate performance.

[0025] In some embodiments of the present disclosure, PD is in the range of 2.3 to 2.7.

[0026] In some embodiments of the present disclosure, PD is in the range of 2.35 to 2.7.

[0027] In this disclosure, D 1 v 50 <D 2 v 50. The D of lithium iron phosphate material 1 v When D is small, the lithium ion diffusion path is relatively short and the fabricated battery has good electrical performance. 2 v When the particle size D of the two materials is large, the compaction density of the positive electrode active material can be increased. vWhen the mixing ratio of the two is within the above range, the mixing ratio of the two lithium iron phosphate materials can be adjusted to ensure that they form a dense mass, and thus the compression density of the resulting positive electrode sheet can be improved without compromising the cycle performance of the battery.

[0028] In some embodiments of the present disclosure, the first lithium iron phosphate material D 1 v 50 is in the range of 0.35 to 0.65, and the D of the second lithium iron phosphate material 2 v 50 is in the range of 1.25 to 2.85.

[0029] In this disclosure, the compressed density PD of the positive electrode sheet and the particle size D of the positive electrode active material mo are considered in combination, rather than pursuing the highest possible PD value. The particle size of the positive electrode active material affects the electronic and ionic conductivity of the electrode sheet. mo can indirectly reflect the content of particles (or fine powder) with a medium to small particle size in the positive electrode active material particles. mo By controlling it to ≦12.38, it is ensured that the positive electrode sheet has an appropriately high packed density, while the overall electronic and ionic conductivity of the positive electrode sheet are both excellent, and the battery has good cycle and rate performance.

[0030] In some embodiments of the present disclosure, PD×D mo is in the range of 0.6 to 10.5. In this case, it is ensured that the positive electrode sheet has a high compression density, and the battery has good electrochemical performance.

[0031] In some embodiments of the present disclosure, D mo is in the range of 0.2 to 4.5. In this case, the positive electrode active material has an appropriate number of small to medium particle sizes, which can ensure that the resistance to ion diffusion / movement inside and between particles of the positive electrode active material is small, contributing to good rate performance and cycle performance of the battery.

[0032] In some embodiments of the present disclosure, D mo is in the range of 0.3 to 4.2.

[0033] In some embodiments of the present disclosure, when the cumulative volume distribution percentage of the positive electrode active material is 50%, the corresponding particle size is D v 50 μm (median particle size), D v 50 is in the range of 0.2~3.1. When the median particle size of the positive electrode active material after mixing is in the above range, the positive electrode active material particles are properly stacked, the polarization strength of the electrode sheet is low, the lithium ion transfer rate during the battery cycle process is high, and the energy density of the secondary battery is high.

[0034] In the present disclosure, the mixing weight ratio of the first lithium iron phosphate material and the second lithium iron phosphate material is not particularly limited as long as it is guaranteed that the particle size of the positive electrode active material formed by mixing the two satisfies the above relational formula.

[0035] In some embodiments of the present disclosure, the mixing weight ratio of the first lithium iron phosphate material to the second lithium iron phosphate material is in the range of 1: (1 to 9), and even in the range of 1: (1 to 4). In this case, the positive electrode active material formed by mixing the two lithium iron phosphate materials can fully guarantee the high compression density of the electrode sheet and the good cycle performance of the battery.

[0036] In some embodiments of the present disclosure, the first lithium iron phosphate material has a carbon coating layer on its surface, and / or the second lithium iron phosphate material has a carbon coating layer on its surface. The carbon coating layer may be obtained by sequentially grinding, spray drying, and sintering a mixed slurry of a phosphorus source, an iron source, a lithium source, and a carbon source. The present disclosure does not limit the specific preparation method of the two lithium iron phosphate materials. Due to the presence of the carbon coating layer, the first and second lithium iron phosphate materials can have good electrical conductivity and have less side reactions with the electrolyte. The positive electrode active material obtained by mixing the two has good electrical conductivity and good cycle performance of the battery.

[0037] According to the positive electrode sheet provided in the first embodiment of the present disclosure, two lithium iron phosphate materials that meet the requirements of specific particle size parameters are mixed, and the particle size D of the positive electrode active material obtained by mixing the two lithium iron phosphate materials is mo The compression density PD of the positive electrode sheet is 0.45≦PD×D mo By controlling the content of the positive electrode sheet to satisfy ≦12.38, it can be ensured that the obtained positive electrode sheet has high compressed density and good electrochemical performance, especially cycle performance and rate performance.

[0038] In some embodiments of the present disclosure, the positive electrode active material layer further includes a binder and a conductive agent. The compressed density of the positive electrode sheet is 2.25 to 2.75 g / cm under a pressure of 1.5 MPa. 3 is in the range.

[0039] In some embodiments of the present disclosure, the positive active material layer is formed by coating a positive paste including a positive active material, a conductive agent, a binder, and a solvent on a positive current collector. The solvent may be one or more of N-methylpyrrolidone (NMP), acetone, and dimethylacetamide (DMAC). The positive current collector includes any one of aluminum foil, carbon-coated aluminum foil, and perforated aluminum foil. The conductive agent includes, but is not limited to, one or more of carbon nanotubes, graphene carbon black, carbon fiber, and the like. The binder includes, but is not limited to, one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA), styrene-butadiene rubber (SBR), polyacrylic acid (PAA), polyacrylate, polyacrylonitrile (PAN), sodium carboxymethylcellulose (CMC), and sodium alginate.

[0040] In a second aspect, the present disclosure provides a lithium-ion battery comprising a positive electrode sheet as described in the first aspect of the present disclosure.

[0041] In some embodiments of the present disclosure, the lithium-ion battery further includes a negative electrode sheet, and an electrolyte and a separator positioned between the positive and negative electrode sheets.

[0042] Lithium-ion batteries using this positive electrode sheet have high energy density and excellent cycle performance.

[0043] The technical solutions of the present disclosure are described below in combination with specific embodiments. EXAMPLES

[0044] The method for making the positive electrode sheet includes the following steps.

[0045] The first lithium iron phosphate material LFP-1 is used, and when the cumulative volume distribution percentage is 50%, the corresponding particle size is 0.55 μm, i.e., D 1 v 50 was 0.55.

[0046] A second lithium iron phosphate material LFP-2 is used, and when the cumulative volume distribution percentage is 50%, the corresponding particle size is 1.35 μm, i.e., D 2 v 50 was 1.35.

[0047] To obtain the positive electrode active material LFP-3, the LFP-1 and LFP-2 materials were mixed in a weight ratio of 2:8. When the volume density of LFP-3 reached a maximum value, the corresponding particle size was 1.15 μm, i.e., D mo was 1.15.

[0048] The positive electrode active material LFP-3 was fabricated into a positive electrode sheet by mixing the LFP-3 material with a binder (specifically, polyvinylidene fluoride, PVDF) and conductive carbon black in a weight ratio of 85:5:10, and adding an appropriate amount of N-methylpyrrolidone (NMP) to mix uniformly to obtain a positive electrode paste. The positive electrode paste was coated on both sides of a carbon-coated aluminum foil and dried to obtain a double-sided positive electrode sheet. The compressed density of the positive electrode sheet was 2.45 g / cm under a pressure of 1.5 Mpa. 3 That is, the PD was 2.45. PD×D of the positive electrode sheet mo was 2.82.

[0049] Preparation of pouch lithium-ion battery: A positive electrode sheet prepared using the positive electrode active material LFP-3 of Example 1 was used as the positive electrode. A graphite electrode sheet was used as the negative electrode. A polypropylene film was used as the separator. A solution containing 1.0 mol / L LiPF6 in ethylene carbonate (EC): dimethyl carbonate (DMC) = 1:1 (volume ratio) was used as the electrolyte. After assembly, a pouch battery was obtained. EXAMPLES

[0050] Different from the method in Example 1, the method for preparing the positive electrode sheet includes the following steps.

[0051] When the first lithium iron phosphate material LFP-1 is used and the cumulative volume distribution percentage is 50%, the corresponding particle size is 0.66 μm, i.e., D 1 v 50 was 0.66.

[0052] A second lithium iron phosphate material LFP-2 is used, and when the cumulative volume distribution percentage is 50%, the corresponding particle size is 1.75 μm, i.e., D 2 v 50 was 1.75.

[0053] To obtain the positive electrode active material LFP-3, the LFP-1 and LFP-2 materials were mixed in a weight ratio of 1:9. When the volume density of LFP-3 reached a maximum value, the corresponding particle size was 1.68 μm, i.e., D mo was 1.68.

[0054] The positive electrode active material LFP-3 obtained in Example 2 was fabricated into a positive electrode sheet according to the method described in Example 1. The compressed density of the positive electrode sheet was 2.59 g / cm under a pressure of 1.5 MPa. 3 That is, the PD was 2.59. PD×D of the positive electrode sheet mo was 4.35. EXAMPLES

[0055] Different from the method in Example 1, the method for preparing the positive electrode sheet includes the following steps.

[0056] When the first lithium iron phosphate material LFP-1 is used and the cumulative volume distribution percentage is 50%, the corresponding particle size is 0.43 μm, i.e., D 1 v 50 was 0.43.

[0057] A second lithium iron phosphate material LFP-2 is used, and when the cumulative volume distribution percentage is 50%, the corresponding particle size is 1.05 μm, i.e., D 2 v 50 was 1.05.

[0058] To obtain the positive electrode active material LFP-3, the LFP-1 and LFP-2 materials were mixed in a weight ratio of 3:7. When the volume density of LFP-3 reached a maximum value, the corresponding particle size was 0.78 μm, i.e., D mo was 0.78.

[0059] The positive electrode active material LFP-3 obtained in Example 3 was fabricated into a positive electrode sheet according to the method described in Example 1. The compressed density of the positive electrode sheet was 2.37 g / cm under a pressure of 1.5 MPa. 3That is, the PD was 2.37. PD×D of the positive electrode sheet mo was 1.85. EXAMPLES

[0060] Different from the method in Example 1, the method for preparing the positive electrode sheet includes the following steps.

[0061] The first lithium iron phosphate material LFP-1 is used, and when the cumulative volume distribution percentage is 50%, the corresponding particle size is 0.35 μm, i.e., D 1 v 50 was 0.35.

[0062] A second lithium iron phosphate material LFP-2 is used, and when the cumulative volume distribution percentage is 50%, the corresponding particle size is 1.79 μm, i.e., D 2 v 50 was 1.79.

[0063] To obtain the positive electrode active material LFP-3, the LFP-1 and LFP-2 materials were mixed in a weight ratio of 4:6. When the volume density of LFP-3 reached a maximum value, the corresponding particle size was 1.22 μm, i.e., D mo was 1.22.

[0064] The positive electrode active material LFP-3 obtained in Example 4 was fabricated into a positive electrode sheet according to the method described in Example 1. The compressed density of the positive electrode sheet was 2.63 g / cm under a pressure of 1.5 MPa. 3 That is, PD was 2.63. PD×D of the positive electrode sheet mo was 3.21. EXAMPLES

[0065] Different from the method in Example 1, the method for preparing the positive electrode sheet includes the following steps.

[0066] When the first lithium iron phosphate material LFP-1 is used and the cumulative volume distribution percentage is 50%, the corresponding particle size is 0.47 μm, i.e., D1 v 50 was 0.47.

[0067] When the second lithium iron phosphate material LFP-2 is used and the cumulative volume distribution percentage is 50%, the corresponding particle size is 1.48 μm, i.e., D 2 v 50 was 1.48.

[0068] To obtain the positive electrode active material LFP-3, the LFP-1 and LFP-2 materials were mixed in a weight ratio of 1:1. When the volume density of LFP-3 reached a maximum value, the corresponding particle size was 1.14 μm, i.e., D mo was 1.14.

[0069] The positive electrode active material LFP-3 obtained in Example 5 was fabricated into a positive electrode sheet according to the method described in Example 1. The compressed density of the positive electrode sheet was 2.67 g / cm under a pressure of 1.5 MPa. 3 That is, PD was 2.67. PD×D of the positive electrode sheet mo was 3.04. EXAMPLES

[0070] Different from the method in Example 1, the method for preparing the positive electrode sheet includes the following steps.

[0071] When the first lithium iron phosphate material LFP-1 is used and the cumulative volume distribution percentage is 50%, the corresponding particle size is 0.91 μm, i.e., D 1 v 50 was 0.91 μm.

[0072] When the second lithium iron phosphate material LFP-2 is used and the cumulative volume distribution percentage is 50%, the corresponding particle size is 2.32 μm, i.e., D 2 v 50 was 2.32 μm.

[0073] To obtain the positive electrode active material LFP-3, the LFP-1 and LFP-2 materials were mixed in a weight ratio of 2:8. When the volume density of LFP-3 reached a maximum value, the corresponding particle size was 3.78 μm, i.e., D mo was 3.78.

[0074] The positive electrode active material LFP-3 obtained in Example 6 was fabricated into a positive electrode sheet according to the method described in Example 1. The compressed density of the positive electrode sheet was 2.56 g / cm under a pressure of 1.5 MPa. 3 That is, PD is 2.56 g / cm 3 The PD×D of the positive electrode sheet mo was 9.68. EXAMPLES

[0075] Different from the method in Example 1, the method for preparing the positive electrode sheet includes the following steps.

[0076] When the first lithium iron phosphate material LFP-1 is used and the cumulative volume distribution percentage is 50%, the corresponding particle size is 0.91 μm, i.e., D 1 v 50 was 0.91 μm.

[0077] When the second lithium iron phosphate material LFP-2 is used and the cumulative volume distribution percentage is 50%, the corresponding particle size is 3.24 μm, i.e., D 2 v 50 was 3.24 μm.

[0078] To obtain the positive electrode active material LFP-3, the LFP-1 and LFP-2 materials were mixed in a weight ratio of 3:7. When the volume density of LFP-3 reached a maximum value, the corresponding particle size was 3.89 μm, i.e., D mo was 3.89 μm.

[0079] The positive electrode active material LFP-3 obtained in Example 7 was fabricated into a positive electrode sheet according to the method described in Example 1. The compressed density of the positive electrode sheet was 2.53 g / cm under a pressure of 1.5 MPa. 3That is, PD is 2.53 g / cm 3 The PD×D of the positive electrode sheet mo was 9.84. EXAMPLES

[0080] Different from the method in Example 1, the method for preparing the positive electrode sheet includes the following steps.

[0081] The first lithium iron phosphate material LFP-1 is used, and when the cumulative volume distribution percentage is 50%, the corresponding particle size is 0.89 μm, i.e., D 1 v 50 was 0.89 μm.

[0082] The second lithium iron phosphate material LFP-2 is used, and when the cumulative volume distribution percentage is 50%, the corresponding particle size is 3.21 μm, i.e., D 2 v 50 was 3.21 μm.

[0083] To obtain the positive electrode active material LFP-3, the LFP-1 and LFP-2 materials were mixed in a weight ratio of 1:9. When the volume density of LFP-3 reached a maximum value, the corresponding particle size was 4.41 μm, i.e., D mo was 4.41 μm.

[0084] The positive electrode active material LFP-3 obtained in Example 8 was fabricated into a positive electrode sheet according to the method described in Example 1. The compressed density of the positive electrode sheet was 2.61 g / cm under a pressure of 1.5 MPa. 3 That is, PD is 2.61 g / cm 3 The PD×D of the positive electrode sheet mo was 11.51.

[0085] To highlight the beneficial effects of the present disclosure, the following comparative examples are provided.

[0086] Comparative Example 1 Different from the method in Example 1, the method for preparing the positive electrode sheet includes the following steps.

[0087] When the first lithium iron phosphate material LFP-1 is used and the cumulative volume distribution percentage is 50%, the corresponding particle size is 0.45 μm, i.e., D 1 v 50 was 0.45.

[0088] A second lithium iron phosphate material LFP-2 is used, and when the cumulative volume distribution percentage is 50%, the corresponding particle size is 3.45 μm, i.e., D 2 v 50 was 3.45.

[0089] To obtain the positive electrode active material LFP-3, the LFP-1 and LFP-2 materials were mixed in a weight ratio of 3:7. When the volume density of LFP-3 reached a maximum value, the corresponding particle size was 4.98 μm, i.e., D mo was 4.98.

[0090] The positive electrode active material LFP-3 obtained in Comparative Example 1 was fabricated into a positive electrode sheet according to the method described in Example 1. The compressed density of the positive electrode sheet was 2.56 g / cm under a pressure of 1.5 MPa. 3 That is, PD was 2.56. PD×D of the positive electrode sheet mo was 12.75, which was outside the range of 0.45 to 12.38 of the present disclosure.

[0091] Comparative Example 2 Different from the method in Example 1, the method for preparing the positive electrode sheet includes the following steps.

[0092] When the first lithium iron phosphate material LFP-1 is used and the cumulative volume distribution percentage is 50%, the corresponding particle size is 1.04 μm, i.e., D 1 v 50 was 1.04, which was outside the range of 0.3 to 0.95 specified in this disclosure.

[0093] When the second lithium iron phosphate material LFP-2 is used and the cumulative volume distribution percentage is 50%, the corresponding particle size is 3.74 μm, i.e., D 2 v 50 was 3.74, which was outside the range of 1.0 to 3.5 specified in this disclosure.

[0094] To obtain the positive electrode active material LFP-3, the LFP-1 and LFP-2 materials were mixed in a weight ratio of 8:2. When the volume density of LFP-3 reached a maximum value, the corresponding particle size was 2.96 μm, i.e., D mo was 2.96 μm.

[0095] The positive electrode active material LFP-3 obtained in Comparative Example 2 was fabricated into a positive electrode sheet according to the method described in Example 1. The compressed density of the positive electrode sheet was 2.53 g / cm under a pressure of 1.5 MPa. 3 That is, PD is 2.53 g / cm 3 The PD×D of the positive electrode sheet mo was 7.49.

[0096] To provide strong support for the beneficial effects of the present disclosure, the pouch cells of each of the examples and comparative examples were tested for the following electrochemical performance.

[0097] 1) Cycle performance: Each pouch battery was subjected to a 0.5C / 0.5C charge-discharge cycle test at 25°C. The voltage range was 2.0-3.8V. During charging, the battery was charged at a constant current of 0.5C up to 3.8V, and then charged at a constant voltage up to a cut-off current of 0.05C. The coulombic efficiency of the first cycle and the capacity retention after 1000 charge-discharge cycles were tested.

[0098] 2) Discharge capacity per gram of positive electrode active material: In the voltage range of 2.0 to 3.8 V, the positive electrode active materials of each Example and Comparative Example were charged to 3.8 V at a constant current of 0.1 C, and then charged at a constant voltage to a cutoff current of 0.05 C. The positive electrode active materials were then discharged to 2.0 V at a constant current of 0.1 C. The charge and discharge process was repeated three times. The third discharge capacity was recorded as C0, and C0 divided by the mass of LFP-3 of each Example and Comparative Example was the capacity per gram of LFP-3.

[0099] Figure 1 shows the cycle performance curves for each of the pouch batteries of Examples 1 to 5 and Comparative Example 1. The coulombic efficiency of the first cycle, the capacity retention after 1000 cycles, and other data for the batteries of each Example and Comparative Example are summarized in Table 1 below. [Table 1]

[0100] As can be seen from FIG. 1 and Table 1, the positive electrode sheet prepared by the method provided in the present disclosure has a higher packing density, and the electrochemical performance of the battery assembled with this positive electrode sheet is excellent. For example, the first cycle Coulombic efficiency can exceed 96%, the positive electrode has a high capacity per gram, and the capacity retention after 1000 cycles is still above 90%. However, the first cycle Coulombic efficiency and cycle performance of the batteries of Comparative Examples 1-2 are poor and are much inferior to the batteries according to the present disclosure.

[0101] The above embodiments only show some implementations of the present disclosure and are described in detail, but they should not be construed as limiting the scope of the present disclosure. It should be understood that a person skilled in the art can make some modifications and improvements without departing from the concept of the present disclosure, and all of them are contemplated within the protection scope of the present disclosure. Therefore, the protection scope of the present disclosure is defined by the appended claims.

Claims

1. A positive electrode current collector; a positive electrode active material layer disposed on at least one side of the positive electrode current collector, the positive electrode active material layer comprising a positive electrode active material, a first lithium iron phosphate material, and a second lithium iron phosphate material; When the cumulative volume distribution percentage of the first lithium iron phosphate material is 50%, the corresponding particle size is D 1 v 50 μm, and when the cumulative volume distribution percentage of the second lithium iron phosphate material is 50%, the corresponding particle size is D 2 v 50 μm, D 1 v 50 is in the range of 0.3 to 0.95, and D 2 v 50 is in the range of 1.0 to 3.5, When the volume density of the positive electrode active material reaches a maximum value, the corresponding particle size is D mo μm, The compressed density of the positive electrode sheet is PDg / cm under a pressure of 1.5 MPa. 3 and PD is 0.45≦PD×D mo ≦12.38, Positive electrode sheet.

2. The positive electrode sheet according to claim 1, wherein PD is in the range of 2.25 to 2.

85.

3. The positive electrode sheet according to claim 1 or 2, wherein PD is in the range of 2.3 to 2.

7.

4. The positive electrode sheet according to any one of claims 1 to 3, wherein PD is in the range of 2.35 to 2.

7.

5. D of the first lithium iron phosphate material 1 v 50 is in the range of 0.35 to 0.65, and the D of the second lithium iron phosphate material 2 v The positive electrode sheet according to any one of claims 1 to 4, wherein 50 is in the range of 1.25 to 2.

85.

6. P.D. mo The positive electrode sheet according to any one of claims 1 to 5, wherein is in the range of 0.6 to 10.

5.

7. D mo The positive electrode sheet according to any one of claims 1 to 6, wherein is in the range of 0.2 to 4.

5.

8. D mo The positive electrode sheet according to any one of claims 1 to 7, wherein is in the range of 0.3 to 4.

2.

9. When the cumulative volume distribution percentage of the positive electrode active material is 50%, the corresponding particle size is D v 50 μm, D v The positive electrode sheet according to any one of claims 1 to 8, wherein 50 is in the range of 0.2 to 3.

1.

10. The positive electrode sheet according to any one of claims 1 to 9, wherein the weight ratio of the first lithium iron phosphate material to the second lithium iron phosphate material is in the range of 1:(1 to 9).

11. The positive electrode sheet according to any one of claims 1 to 10, wherein the first lithium iron phosphate material has a carbon coating layer on a surface thereof, and / or the second lithium iron phosphate material has a carbon coating layer on a surface thereof.

12. The positive electrode active material layer further comprises a binder and a conductive agent, and the compressed density of the positive electrode sheet is 2.25 to 2.75 g / cm under a pressure of 1.5 MPa. 3 The positive electrode sheet according to claim 1 , wherein the surface area of ​​the positive electrode sheet is in the range of 0.1 to 1.0 mm.

13. The positive electrode sheet according to claim 12 , wherein the positive electrode active material layer is formed by coating a positive electrode paste comprising the positive electrode active material, a conductive agent, the binder, and a solvent on the positive electrode current collector.

14. A lithium ion battery comprising the positive electrode sheet according to any one of claims 1 to 13.

15. 15. The lithium ion battery of claim 14, further comprising a negative electrode sheet, and an electrolyte and a separator located between the positive and negative electrode sheets.

Citation Information

Patent Citations

  • High-compaction-density lithium iron phosphate and preparation method thereof

    CN107256968A

  • High-compaction-density lithium iron phosphate anode material and preparation method thereof

    CN108011104A

  • A lithium iron phosphate with high compact density and a preparation method thereof

    CN109192948A

  • Positive electrode material lithium iron phosphate and preparation method thereof

    CN109665508A

  • High-compaction low-temperature lithium iron phosphate material, lithium battery positive plate and preparation method thereof

    CN113086959A